ANALISA PERBAIKAN KINERJA PENGIRIMAN PRODUK R754046 DI PT PELANGI ELASINDO DENGAN PENDEKATAN SAFETY STOCK - Joko Hardono (Jurnal Teknik, 2020)
PT Pelangi Elasindo is one of the leading manufacturers in Indonesia specializing in webbing production, shoelaces, cords, high quality Molded Pulp, elastics and tape. As one of the vendors for leading shoe factories in the world, the accuracy of shipping goods both in terms of quantity and time is very important because this is a benchmark for calculating shipping performance. There was a delay in delivery at PT Pelangi Elasindo on the R7540460000 Molded Cardboard Shape size 2 product, making delivery performance decrease. Delivery performance in January is 93% while the minimum delivery performance standard is 95%. This study aims to analyze the factors that delay the delivery of goods to customers and improve delivery performance. Based on the results of the analysis, the factors that cause the delay in delivery are damage to the machine, manual cutting and demand variations and uncertainty of lead time. Among these factors, demand variations and lead time uncertainty are the most influential factors, so to improve delivery performance, safety stock must be prepared to avoid stock outs and delivery delays. Based on the results of the calculation of the safety stock that must be prepared is 8,403 prs per week. Key words : Delivery, performance, safety stock,improve